The Responsibility of Midwives in Implementing Early Breastfeeding Initiation as the Right of Newborns Based on Law Number 17 of 2023 Concerning Health - Hempi Wanty Saragih (JURNAL HUKUM SEHASEN, 2026)
Early Initiation of Breastfeeding (IMD) is an important step in providing exclusive breastfeeding (ASI) which plays a major role in reducing infant mortality and improving maternal and infant health. Midwives as health workers have a moral, professional, and legal responsibility in ensuring the implementation of IMD in accordance with Law number 17 of 2023 concerning Health. This study aims to analyze the responsibilities of midwives in implementing IMD based on the provisions of the regulation. The planned research method is a library research with a descriptive qualitative approach, through analysis of various academic sources such as journals, books, and related official regulations. The results of the analysis indicate that midwives' responsibilities include implementing IMD according to Standard Operating Procedures (SOP), providing education to pregnant and breastfeeding mothers, and ensuring the baby's right to receive breast milk immediately after birth. In addition, it was found that the level of knowledge, attitudes, and support from health facilities have a significant influence on the success of IMD implementation. Based on the analysis of Law number 17 of 2023, midwives have a strategic role in supporting the national policy of exclusive breastfeeding, both as implementers, educators, and supervisors in health care facilities. The conclusion of this study shows that the responsibility of midwives in implementing IMD is not only an ethical and professional obligation, but also an implementation of legal protection for the rights of newborns to receive exclusive breastfeeding.